Liposarcoma of the paratesticular tissue and spermatic cord: A case report - Vukmirović Filip; Zejnilović Nihad; Ivović Jovan (Vojnosanitetski Pregled)
Introduction. Liposarcomas are malignant tumors derived from fat tissues. Liposarcoma of the paratesticular tissue is rare. Case report. We presented a 51-year-old man with liposarcoma of paratesticular tissue and the spermatic cord, mimicking a testicular tumor. Ultrasound examination of this scrotal mass was hyperechogenic and homogeneous and separated from the testis and epididymis. The patient was operated, and the orchidectomy was performed. Histology revealed well-differentiated lipoma-like liposarcoma of the paratesticular tissue and spermatic cord. After a 6 month follow-up the patient did not show any evidence of tumor-progression or recurrence. Conclusion. Liposarcomas of the paratesticular tissue and seminal cord represent a rare type of tumors, often misdiagnosed preoperatively. Therapy should include radical surgical excision, usually radical inguinal orchiectomy. If the margin status is in doubt, adjuvant radiation should be performed. Local relapse is common and may occur after several years, so follow- up period has to be sufficiently long.